2014
DOI: 10.5812/ijem.17796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypomagnesaemia among Obese Type 2 Diabetic Patients Attending the National Center for Diabetes, Endocrinology and Genetics (NCDEG)

Abstract: Background:Some observations suggested that magnesium supplementation could be helpful in the treatment of diabetic patients by improving glycemic control and preventing the development of diabetes-related complications.Objectives:To estimate the prevalence of hypomagnesaemia among obese patients with type 2 diabetes attending the National Center for Diabetes, Endocrinology and Genetics (NCDEG) in Amman, Jordan.Patients and Methods:A cross-sectional study was carried out at the National Center for diabetes, En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
5
21
1
1
Order By: Relevance
“…Serum magnesium levels are associated with insulin resistance and β cell function in patients with diabetes. Furthermore, magnesium deficiency is associated with decreased β cell function and increased insulin resistance, leading to elevated plasma glucose levels [ 4 6 ]. Dietary supplementation with magnesium may decrease the risk of developing diabetes [ 7 , 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum magnesium levels are associated with insulin resistance and β cell function in patients with diabetes. Furthermore, magnesium deficiency is associated with decreased β cell function and increased insulin resistance, leading to elevated plasma glucose levels [ 4 6 ]. Dietary supplementation with magnesium may decrease the risk of developing diabetes [ 7 , 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia has been reported in 13.5% to 47.7% of nonhospitalized patients with type 2 diabetes compared to a prevalence of 2.5% to 15% in nonhospitalized patients without diabetes [ 3 ]. Low levels of magnesium have been associated with increased insulin resistance, the presence of type 2 diabetes mellitus, or even diabetes medication [ 4 6 ]. Dietary supplementation with magnesium may alleviate insulin resistance and decrease diabetes risk.…”
Section: Introductionmentioning
confidence: 99%
“…Various cross‐sectional and longitudinal studies confirms the association of Mg intake with insulin sensitivity and glucose homeostasis . Two meta‐analyses have been conducted aiming to determine the effect of Mg supplementation on insulin sensitivity and glucose homeostasis (involving an intervention duration of 4–24 weeks with both organic and inorganic salt forms).…”
Section: Introductionmentioning
confidence: 99%
“…Mg is considered to be an independent predictor of type 2 diabetes progression [25,27,28] and its complications [8,29,30], and clinical experiments have confirmed that Mg supplementation can improve hyperglycemia, oxidative stress, and inflammatory response in diabetic patients [31]. Zhang [7] and other investigators [18,32,33] demonstrated that serum Mg was lower in patients with diabetes, and Zhang [7] found that Mg was associated with parameters reflecting nerve conduction efficacy in DPN patients [7]. It has been stated that diabetes is characterized with negative Mg balance [20], for reduced gastrointestinal Fig.…”
Section: Alternation In Elements Of Serum and Urine Of Control And Dpmentioning
confidence: 99%